THE DEVELOPMENT OF NOTCH STRESS METHOD AND ITS’APPLICATION IN THE FATIGUE ANALYSIS OF WELDED STRUCTURES - LIU Xu; ZHOU ChunPing; ZHANG KaiLin; YAO Yuan (Jixie qiangdu)
The notch stress method（ NSM） is a local fatigue analysis method of welded structure,this method has high accuracy because it focus on the analysis of strain and stress of the fatigue weak area,such as weld toe and weld root. The article collected relevant literature of recent years,so the development history and basic principles of notch stress method had been reviewed; the similarities and differences of nominal stress method,structure stress method,and notch stress method were also summarized. Then latest research progress and development trend of this method were introduced from the following three aspects: the reasonable values of fictitious notch radii; the fatigue class assessment（ FAT） of notch; the slopes of notch fatiguelife curves. In the last but not least,the article showed some welded structures application examples of fatigue analysis with NSM in several industrial areas. Through the comprehensive introduction of notch stress method in this paper,it aims to provide beneficial reference for the domestic welded structure fatigue strength design.